Direct torque control of induction motor for speed control using back propagation in artificial neural network / Muhammad Khairul Arifin Abd Aziz - Abd Aziz, Muhammad Khairul Arifin (2004)
This report presents Artificial Neural Network controller for direct torque control, (DTC) induction motor drives. ANN speed controller for an induction motor which behaves similar to PI (Proportional and integral) controller. The model of induction motor is designed using the relevant equations. A closed-loop system is used for testing. The induction motor speed is control by ANN Technique using samples obtained from the classical technique (PI controller) and Direct Torque Control (DTC) controller. The data for training ANN is generated by simulating a model of the induction motor using SIMULINK. In supervised session, back propagation method will be applied in ANN programs. Comparison is made between classical technique and ANN technique.